2016
DOI: 10.3892/ol.2016.5329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IL-17 in the development of colon cancer in mice

Abstract: Cytokine therapy is commonly used for tumor immunotherapy. Although early studies focused directly on the tumor, current investigations are more attentive of the tumor microenvironment. Various immune cells and related cytokines in the tumor microenvironment play an important role in the occurrence and development of tumor. Interleukin (IL)-17 is the characteristic cytokine produced by Th17 cells. IL-17 has been associated with various immune responses. The results of previous studies showed that IL-17 can sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…For instance, Kryczek et al reported that subcutaneous injection of the MC38 murine colon cancer cell line into IL-17-deficient mice resulted in faster growth and increased lung metastasis foci compared to that of wildtype control mice (85). Previous studies have demonstrated that the antitumor effect of IL-17 in various cancer types is related to enhanced recruitment and activity of lymphocytes, natural killer (NK) cells, and DCs into the tumor site and production of the antitumor cytokine IFN-γ (8689). Lin et al showed that CRC patients with higher IL-17 levels tend to have a better prognosis than those with lower IL-17 levels (90).…”
Section: The Role Of Th9/il-9 Th17/il-17 and Th22/il-22 In The Devementioning
confidence: 99%
“…For instance, Kryczek et al reported that subcutaneous injection of the MC38 murine colon cancer cell line into IL-17-deficient mice resulted in faster growth and increased lung metastasis foci compared to that of wildtype control mice (85). Previous studies have demonstrated that the antitumor effect of IL-17 in various cancer types is related to enhanced recruitment and activity of lymphocytes, natural killer (NK) cells, and DCs into the tumor site and production of the antitumor cytokine IFN-γ (8689). Lin et al showed that CRC patients with higher IL-17 levels tend to have a better prognosis than those with lower IL-17 levels (90).…”
Section: The Role Of Th9/il-9 Th17/il-17 and Th22/il-22 In The Devementioning
confidence: 99%
“…In this study IL-17concentration was significantly elevated after the drug modality that promotes to control the adenocarcinoma of colon. It was revealed that PUMA controlled tumour growth by inhibiting cell cycle progression and by stimulating apoptosis [17]. In this study, the concentration of PUMA was increased after treatment.…”
Section: Resultsmentioning
confidence: 54%
“…In this study, the data showed that IL-17 expression had a negative correlation with the expression of FAS and FASL. A previous study highlighted IL-17 to be a potential prognostic marker for patients with respiratory, digestive, and other system cancers [ 13 ]. In addition, IL-17 may be significantly correlated with the differentiation and angiogenesis in the development of LC as the expression of CXCL9, CXCL10, and IL-17 mRNAs in the skin of FAS- and FASL-deficient mice was decreased [ 27 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%